2020
DOI: 10.21203/rs.3.rs-47390/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome analysis identifies genes involved in the somatic embryogenesis of Eucalyptus

Abstract: Background: Eucalyptus, a highly diverse genus of the Myrtaceae family, is the most widely planted hardwood in the world due to its increasing importance for fiber and energy. Somatic embryogenesis (SE) is one large-scale method to provide commercial use of the vegetative propagation of Eucalyptus and dedifferentiation is a key step for plant cells to become meristematic. However, little is known about the molecular changes during the Eucalyptus SE.Results: We compared the transcriptome profiles of the differe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Callus is like the meristematic tissues, which is a self-renewing structure consisting of stem cells and their immediate daughters (Springer and Kohn, 1979; Xiao et al, 2020), but the mechanism on how to maintain this self-renewing structure is unclear. Reactive oxygen species (ROS) play an important role in maintaining plant cell proliferation (Vemoux et al, 2000; Wells et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Callus is like the meristematic tissues, which is a self-renewing structure consisting of stem cells and their immediate daughters (Springer and Kohn, 1979; Xiao et al, 2020), but the mechanism on how to maintain this self-renewing structure is unclear. Reactive oxygen species (ROS) play an important role in maintaining plant cell proliferation (Vemoux et al, 2000; Wells et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our lab published the transcriptome and miRNA profiles of tissue-culture induced callus of two Eucalyptus species-E. camaldulensis (high regeneratively potential) and E. grandis x urophylla (low regenerative ability) [2,28,29]. We found that early stage of SE is important for downstream callus development as it prepares for the acquisition of SE potential of callus via dedifferentiation on transcriptional level [2].…”
Section: Introductionmentioning
confidence: 99%
“…Since Steward firstly reported the asexual embryogenesis in the cell suspension cultures of carrot in 1958, in vitro SE systems have been established in many plant species [1]. For Eucalyptus -a highly diverse genus of the Myrtaceae family widely planted across the world for its increasing importance for timber and pulp [2,3], Ouyang et al reported the SE from the callus of seedlings for the first time in 1980 [4]. Early SE is the callus induction in which differentiated somatic cells (e.g., seed, leaf, stem) acquire embryogenetic competence with or without a dedifferentiation step [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many plant species have been examined for the characterisation of genes particularly expressed during somatic embryogenesis, including wheat (Chu et al, 2017), cotton (Zeng et al, 2006; Wu et al, 2009; Cheng et al, 2016; Cao et al, 2017), peanut (Rani et al, 2005), carrot (Aleith and Richter, 1991), grape (Gianazza et al, 1992), alfalfa (Domoki et al, 2006), conifer (John and Gerald, 2007; Yakovlev et al, 2016), papaya (Jamaluddin et al, 2017), maize (Salvo et al, 2014) and banana (Enríquez-Valencia et al, 2019). These studies have identified genes that are differentially expressed in SE, including SOMATIC EMBRYOGENESIS RECEPTOR KINASE (SERK) (Schmidt et al, 1997), LEAFY COTYLEDON (LEC) (Curaba et al, 2004), ABSCISIC ACID INSENSITIVE3 (ABI3), FUSCA3 (FUS3) (Freitas et al, 2019), BABY BOOM (BBM) (Boutilier et al, 2002; Maulidiya et al, 2020), WUSCHEL (WUS) (Zuo et al, 2002,), AUXIN RESPONSE FACTOR 19 (ARF19) (Xiao et al, 2020), and LATE EMBRYOGENESIS ABUNDANT (LEA) protein (Wickramasuriya and Dunwell, 2015; Jamaluddin et al, 2017). Although RNA-Seq (RNA Sequencing) analyses have been conducted to investigate genome-wide gene expression in response to somatic embryogenesis (SE) in many plants, the expressions of genes involved along with the key factors determining gene changes and regulations in somatic embryo maturation in cereals have not been previously investigated.…”
Section: Introductionmentioning
confidence: 99%